Off-label use of ceftiofur in one-day chicks triggers a short-term increase of ESBL-producing E. coli in the gut. - Mauro M S Saraiva; Alexandre L B Moreira Filho; Oliveiro C Freitas Neto; Núbia M V Silva; Patrícia E N Givisiez; Wondwossen A Gebreyes; Celso J B Oliveira (PLoS ONE, 2018)
This trial was designed to evaluate the off-label use of ceftiofur with Marek's vaccine in one-day-old broiler chicks, a prophylactic treatment that has been done in some commercial hatcheries, on the emergence of extended-spectrum beta-lactamase producing Escherichia coli (ESBL-E. coli). A total of 168 chicks (Cobb500®) were used in a completely randomized design. Birds were assigned to two treatments (Marek's vaccine plus saline vs Marek's vaccine plus ceftiofur) and six repetitions, with 14 animals each. Cloacal swabs were collected from 1 to 14 days post-hatch. The majority (86%; p<0.0001) of the ESBL-producing isolates harboring blaCTX-M and blaSHV genes originated from animals receiving the antimicrobial. None of the isolates were positive for plasmid-mediated AmpC betalactamase genes (blaACC, blaCMY-2, blaDHA, blaFOX, blaMOX and blaMIR). These findings indicate that the off-label use of ceftiofur with Marek's vaccine is associated with the short-term increase in ESBL-producing Escherichia coli in the gut of chicks.